Antibacterial Activity and Structure Elucidation of Salicin from Stem Bark of Salix tetrasperma ROXB. - Sari Ramadhani; Adlis Santoni; Mai Efdi (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2019)
Salix tetrasperma Roxb. (Family Salicacaeae) is a plant that used as traditional medicine for anti-inflammatory, analgesic, reduces fever, and itching medicine. In this study was carried out extraction, isolation, structure elucidation of salicin from Salix tetrasperma Roxb. stem bark and it’s antibacterial activity. The extraction method was used the maceration method by n-hexane, ethyl acetate, and methanol solvents. Isolation of compound from ethyl acetate extract of Salix tetrasperma Roxb. stem bark using chromatography methods and obtained white solid (15 mg). The structure was elucidated using spectroscopic analysis, including Ultraviolet (UV), Infrared (IR), Nuclear Magnetic Resonance (NMR) and comparative literature, identified as salicin compound with molecule formula C13H18O7. Antibacterial activity was evaluated against Escherichia coli and Staphylococcus aureus bacteria using disk diffusion method. This compound has a great an antibacterial activity against Staphylococcus aureus bacteria with clear zone diameter of 10.2 ± 0.3 mm. This shows that the Salix tetrasperma Roxb. stem bark has great potential as a source of antibacterial compound